The Hemocompatibility of Nanoparticles: A Review of Cell–Nanoparticle Interactions and Hemostasis - Kara M. de la Harpe; Pierre P.D. Kondiah; Yahya E. Choonara; Thashree Marimuthu; Lisa C. du Toit; Viness Pillay (Cells, 2019)
Understanding cell–nanoparticle interactions is critical to developing effective nanosized drug delivery systems. Nanoparticles have already advanced the treatment of several challenging conditions including cancer and human immunodeficiency virus (HIV), yet still hold the potential to improve drug delivery to elusive target sites. Even though most nanoparticles will encounter blood at a certain stage of their transport through the body, the interactions between nanoparticles and blood cells is still poorly understood and the importance of evaluating nanoparticle hemocompatibility is vastly understated. In contrast to most review articles that look at the interference of nanoparticles with the intricate coagulation cascade, this review will explore nanoparticle hemocompatibility from a cellular angle. The most important functions of the three cellular components of blood, namely erythrocytes, platelets and leukocytes, in hemostasis are highlighted. The potential deleterious effects that nanoparticles can have on these cells are discussed and insight is provided into some of the complex mechanisms involved in nanoparticle–blood cell interactions. Throughout the review, emphasis is placed on the importance of undertaking thorough, all-inclusive hemocompatibility studies on newly engineered nanoparticles to facilitate their translation into clinical application.